2001
DOI: 10.1007/bf03020368
|View full text |Cite
|
Sign up to set email alerts
|

Souffrance cérébrale sous anesthésie générale: que peut-on attendre de la surveillance de l’EEG?

Abstract: L existe, au cours de la période périopératoire, de multiples circonstances pouvant favoriser une souffrance cérébrale, du bas débit cardiaque (souffrance diffuse), à l'obstruction artérielle (thrombose, embolie, spasme, clampage, etc.) ou aux lésions du parenchyme (oedème, hémorragie ou hypoxémie). Ces circonstances surviennent plus volontiers dans certains types de chirurgie, comme la chirurgie cardiaque ou carotidienne qui sont considérées à haut risque d'accident neurologique.La survenue d'une souffrance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, BIS affects the decision to decrease doses of anesthetic agents to prevent cardiovascular instability, including hypotension, without increasing the risk of intraoperative awareness in elderly or critically ill patients. However, despite its usefulness, the BIS as an indicator of level of consciousness should be interpreted with caution, since it is influenced by many factors including electrical interference, air vibration, and altered cerebral perfusion 912 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BIS affects the decision to decrease doses of anesthetic agents to prevent cardiovascular instability, including hypotension, without increasing the risk of intraoperative awareness in elderly or critically ill patients. However, despite its usefulness, the BIS as an indicator of level of consciousness should be interpreted with caution, since it is influenced by many factors including electrical interference, air vibration, and altered cerebral perfusion 912 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that sudden decrease in cerebral perfusion was associated with lower BIS value. [3456]…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a recent change in anesthetic concentration, a sudden change in the EEG including increased delta activity, periods of burst suppression, or persistent suppression, 54-56 and/or a decrease in the BIS value, may suggest ischemia. It has long been recognized that sudden EEG changes during CPB could be attributable to such problems as superior vena cava obstruction, generalized decrease in cardiac output, and other malfunctions of the CPB apparatus.…”
Section: Cerebral Ischemiamentioning
confidence: 99%
“…In an editorial Billard indicated that unprocessed EEG monitoring is not absolutely reliable at detecting brain injury. 54 It appears reasonably specific when anesthesia is stable but it is not very sensitive, meaning that a stable, unchanged EEG is of limited value in excluding ischemia. Similarly, BIS and raw EEG may be useful for detecting brain ischemia, especially when anesthesia is stable, if the insult is sudden, extended or located in the frontal area, and if the preoperative EEG was normal.…”
Section: Cerebral Ischemiamentioning
confidence: 99%